Petri net models of discrete logics used in control algorithms developed in ladder diagram language - Quezada, José Carlos; Flores, Ernesto; Baños, Esperanza; Quezada, Víctor (International journal of advanced manufacturing technology, 2023)
Control algorithms for programmable logic controllers are still developed based on the experience of those responsible for control in the industry. The IEC-61131-3 standard considers five programming languages: Ladder Diagram, Structured Text, Function Block Diagram, Instruction List, and Sequential Function Diagram, which use different function blocks to develop control algorithms. Within the control algorithms for discrete event systems, there are two types of blocks: those with discrete inputs and outputs, and those with discrete and analog inputs and discrete output. Of the latter, the present research shows the analysis and formal model of the blocks including the problems of accumulation of tokens and the restoration of the coils. This proposal includes logical blocks of timers, counters, positive and negative transition detectors and bistable elements, which, together with the AND, OR, AND-OR, contact lock, auto-loop and Set-Reset logics, can be modeled and analyzed control algorithms with a greater degree of complexity. This guarantees the safety of workers as well as machines.